The Effect of Using the Make A Match Learning Model on Students' Critical Mathematical Thinking Skills - Permatasari, Azmi Endah; Wahyudin, Wahyudin (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2021)
This research aims to determine the effect of the use of making a match learning model on students' critical mathematical thinking abilities. This study used a quasi-experimental method non-equivalent pretest-posttest control design with a population of grade V students in SD Plus Al Aitaam selected two classes consisting of experimental classes with a total of 24 students and control classes with a total of 24 students. The research began with the giving of tests in the form of a pretest, then given treatment, and ended with a posttest. The results study shows that students' mathematical critical thinking skills using the Make a match type cooperative is better than those studied using conventional models. This is evidenced by the average posttest score obtained by the experiment class = 85.96 while the control class= 79.92. That way the average experiment class is higher than the control class. Supported with t-test results showing tcount= 5.54 and, ttable= 2.06 Because the value tcount> is then ttable accepted Ha, So, there is a difference in mathematical thinking skills between students who learn using a cooperative learning model of type make a match with students who get learning using conventional models.